1998
DOI: 10.1007/s002770050455
|View full text |Cite
|
Sign up to set email alerts
|

Significance of p53 overexpression in bone marrow biopsies from patients with bone marrow failure: aplastic anemia, hypocellular refractory anemia, and hypercellular refractory anemia

Abstract: Among patients with bone marrow failure, differentiating acquired aplastic anemia (AA) from hypocellular refractory anemia (hypo RA) can be a difficult and challenging task. Morphological, cytochemical, immunocytochemical, and cytogenetic studies may provide tools for discriminating between both entities. In addition, differences in the pattern of proliferation and apoptosis of bone marrow cells in AA and in the myelodysplastic syndrome have been reported. Because of the correlation between p53 and apoptosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 19 publications
2
20
0
3
Order By: Relevance
“…58 Clearly, similar to the pathological role of p53 in bone marrow developmental defects, 59 p53, when abnormally active, also serves as a pathogenic agent in Down syndrome development.…”
Section: Role Of the P53-mir-1246-dyrk1a-nfat Pathway In Down Syndromementioning
confidence: 99%
“…58 Clearly, similar to the pathological role of p53 in bone marrow developmental defects, 59 p53, when abnormally active, also serves as a pathogenic agent in Down syndrome development.…”
Section: Role Of the P53-mir-1246-dyrk1a-nfat Pathway In Down Syndromementioning
confidence: 99%
“…Myelodysplastic syndrome is characterized by dysplastic and ineffective normocellular or hypercellular bone marrow with variable degree of peripheral blood cytopenia along with higher risk of transformation to acute myeloid leukemia (AML). However, 8-46% patients of MDS have hypoplastic bone marrow [2]. In this situation, it is often very diffi cult to determine whether the patient has AA or hypoplastic MDS (HMDS).…”
Section: Introductionmentioning
confidence: 99%
“…Various attempts have been made in the past to differentiate these entities using morphological, histological and conventional cytogenetics [1][2][3][4][5][6][7][8][9][10][11]. In addition, differences in the pattern of proliferation of bone marrow cells in AA and MDS have been reported [2,[12][13] through immunohistochemistry techniques using several antigens (p53, proliferating cell nuclear antigen i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These diagnostic challenges underline the role of bone marrow histology with a panel of immunohistochemical markers in the work-up of unclear cytopenias with/without dysplasia. Immunohistochemical staining for p53 may provide additional information to help differentiate hypoplastic MDS from AA [23,24]. Strong nuclear p53 staining has in previous studies been shown to be useful as both a diagnostic and a prognostic marker [25,26], and may be associated with an underlying TP53 mutation [27].…”
Section: Cytopenia With Clonal Haematopoiesis Not Fulfilling Mds Critmentioning
confidence: 99%